1993
DOI: 10.1172/jci116276
|View full text |Cite
|
Sign up to set email alerts
|

Role of pH in determining the cell-type-specific residual activity of glucocerebrosidase in type 1 Gaucher disease.

Abstract: The properties of control and 370Asn --Ser glucocerebrosidase, the frequently encountered mutated form of the enzyme in type 1 Gaucher disease, were studied in vitro as well as in situ.The catalytic properties of purified 37Asn -* Ser glucocerebrosidase were highly dependent on the assay conditions. The enzyme was deficient in activity towards substrate and in reactivity with the irreversible inhibitor conduritol B-epoxide (CBE) when activated by the bile salt taurocholate. In the presence of more physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…Concentrations of BMP and other lipids in the lysosomal compartment may vary tremendously between different cell types, and also between lysosomes of one and the same cell due to local fluctuations between influx rates into individual lysosomes and catabolic rates of lipids within individual lysosomes. Local lysosomal conditions may be even more critical for some mutant lysosomal hydrolases, e.g., for mutant GBA1 (89). In Niemann-Pick type C disease, characterized by the cholesterol primary storage, GlcCer secondary accumulation could be triggered by SM secondary accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of BMP and other lipids in the lysosomal compartment may vary tremendously between different cell types, and also between lysosomes of one and the same cell due to local fluctuations between influx rates into individual lysosomes and catabolic rates of lipids within individual lysosomes. Local lysosomal conditions may be even more critical for some mutant lysosomal hydrolases, e.g., for mutant GBA1 (89). In Niemann-Pick type C disease, characterized by the cholesterol primary storage, GlcCer secondary accumulation could be triggered by SM secondary accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of the lysosome is important in determining the activity of a least one common glucocerebrosidase mutant protein; its activity is nearly normal at pH 5 but declines markedly when the pH is lowered. 42 Thus, some of the variability characteristic of this disease might be attributable to individual differences, hereditary or environmental, in the pH of lysosomes.…”
Section: Gaucher Diseasementioning
confidence: 99%
“…The differences in results do not seem to be due to the method used, since a range of results were reported for the same method. It was suggested that the low activity of the N370S mutant enzyme may depend on the pH of the assay [Vanweely et al, 1993]. However, we tested the N370S enzyme activity at several pH values without finding significant differences in its maximal activity between pH 5.0 and 5.7.…”
Section: Discussionmentioning
confidence: 92%